Uma compreensão fenomenológica hermenêutica da experiência do tédio: narrativas do setting terapêutico. - Albuquerque, Tatiany Maria Melo Silva (2024)
Boredom throughout history has been understood as an emotion and, in this sense, it tends to be considered a momentary mood state related to changes in mood experienced by individuals in their daily lives. It is hardly framed as existential. Heidegger, when proposing this reading of boredom, points out that it can have three forms of presentation: embodied or materialized boredom; boredom with no apparent explanation; and, finally, deep boredom, the latter considered a fundamental affective tone, that is, a given tuning or tune between Dasein and the world. The present work is the result of an investigation in which we sought to understand the experience of boredom in the clinical setting based on the narratives of psychotherapists. The research methodology with a qualitative approach of a hermeneutic phenomenological nature was adopted. Data were collected through oral testimony from research collaborators, evoked by a triggering question. As a method of understanding and interpreting the statements, conversation and the construction of constellations guided by Gadamer's thinking were used. The results reveal that the phenomenon of boredom was revealed in two ways in the participants' clinical listening: as the main affective tone and with the predominance of other tones. In this context, the dialogical-hermeneutic dimension points to the possibility of the liberating character of clinical action that moves away from the parameters of modern technique and considers the particularities of being-there in its context and culture, being, therefore, attentive to transformations and seeking a deep understanding of boredom as an affective tone that reveals itself in different modes of existence.